George Eliot as a Realist - Dille, Mary Alberta (My University, 1900)
Introduction: Among the great English novelists of the nineteenth century, who were moving forces in the great world of that time, George Eliot occupies a foremost place as representative of the realistic style of literature. And not only of that time was she a moving force: her influence today is as strong as it was then, and will continue so to be, because of the permanency and universality of her works; permanent in that they express feelings which are common to people of all times, and universal, because no country is free from such characters as she deals with. Rarely do we find an intellect so perfectly contented in its sphere, as hers, in its exponent of human life – of human life as found among the weak, the uneducated, and the unpolished. An English writer ranks her next to Shakespeare in her power to picture the tragedy underlying such life by artfully analyzing character and unravelling the web of complex human motives. After reading one of her best works illustrative of this power, we feel that we have witnessed the life of a man of the world, and not of an imaginary being who exists only in a book. With her, we visit the homes of these common-place people, busy in the workshop, on the farm; we go with the solitary outcast from place to place, see the evil, the frustrations and the distress prevalent among the middle classes, and the outward influences active upon their lives, just asa today influences are present upon similar lives, making them better or worse.
Citation: Dille, Mary Alberta. George Eliot as a Realist. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Climate; Horticulture; Euphorbia Cananensis; Papilioinaceae; Asparagineae; Plygalaceae; Theses; Manuscripts (documents)